2019
DOI: 10.1177/2158244019893700
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing Criminology: Social Media and Citizen Policing in Missing Person Cases

Abstract: Criminology is undergoing a process of innovation and experimentation with the rise of social media. Although police have traditionally been the locus of legal enforcement, ordinary citizens are increasingly afforded opportunities to participate in crowdsourced investigations. In this article, we explore the emerging field of crowdsourcing criminology and its relationship to newsmaking criminology, public criminology, and the reshaping of news as infotainment (popular criminology). Drawing on a case study of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Textual analysis of policies addressing MMIWG was the focus of one study (Rothenberg, 2019). Four studies used large data through crowdsourcing (Gray & Benning, 2019) and social media (Moeke-Pickering et al, 2018; Parsloe & Campbell, 2021) to examine the #MMIW social movement. One study (Desmoulins, 2019) interviewed individuals after they had attended the “Walking with Our Sisters” exhibit on MMIWG, asking the participants about their reactions to the exhibit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Textual analysis of policies addressing MMIWG was the focus of one study (Rothenberg, 2019). Four studies used large data through crowdsourcing (Gray & Benning, 2019) and social media (Moeke-Pickering et al, 2018; Parsloe & Campbell, 2021) to examine the #MMIW social movement. One study (Desmoulins, 2019) interviewed individuals after they had attended the “Walking with Our Sisters” exhibit on MMIWG, asking the participants about their reactions to the exhibit.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported that tribal members were unaware of victim services (Koch et al, 2022) and assumed if they reported to law enforcement they would not be believed (Murphy-Oikonen et al, 2022; Olson-Pitawanakwat & Baskin, 2021; Parloe & Campbell, 2021). One way to raise awareness of missingness among Indigenous women and girls that was suggested in several studies is to use a variety of media formats (Gray & Benning, 2019; Huey & Ferguson, 2020; Joseph, 2021; Moeke-Pickering et al, 2018; Parloe & Campbell, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doctors and medical researchers, for instance, have come to confront data produced by patients through online personal diaries, patient communities, or social media (Kallinikos and Tempini 2014). Prosecutors and police officers nowadays deal regularly with evidence produced for infotainment and information hunting via crowdsourcing platforms (Gray and Benning 2019). Social media data are routinely used to make investment decisions in finance or to compute credit scores for insurance companies (O'Neil 2016).…”
Section: Digital Data and Knowledgementioning
confidence: 99%
“…Social media allows potentially millions of users to view these images and then identify the subjects in them. In the case of searching for perpetrators of crimes, these efforts often identify assailants, such as Boston Marathon bomber or members of hate groups (Douglas, 2020;Gray & Benning, 2019;Nhan et al, 2017). However, these efforts sometimes become an exercise in vigilantism and deviate from true crowdsourced efforts as they lack a clear crowdsourcer or a clear criminal justice purpose; moreover, if the target is misidentified, there is no clear response to remedy the error (Chang & Poon, 2017;Douglas, 2020;Loveluck, 2019).…”
Section: Crowdsourcing Data and Solutionsmentioning
confidence: 99%